2017
DOI: 10.1002/smll.201700044
|View full text |Cite
|
Sign up to set email alerts
|

Strong Improvement of Long-Term Chemical and Thermal Stability of Plasmonic Silver Nanoantennas and Films

Abstract: Silver (Ag) nanostructures and thin films are advantageous plasmonic materials as they have significantly lower losses than gold (Au). Unfortunately, Ag nanostructures suffer from poor chemical and thermal stability, which limit their applications. Here, the mechanisms leading to the deterioration of Ag nanostructures are clarified. It is first shown that oxygen alone cannot oxidize Ag nanostructures. Then, experiments using X‐ray photoelectron spectroscopy reveal that the amount of sulfur in ambient air is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 95 publications
(122 reference statements)
0
62
0
Order By: Relevance
“…This drastically restricts the choice of emitters available for quantum plasmonic experiments [16][17][18] . In contrast to gold, silver leads to reduced losses in the visible spectral range [19][20][21] although care has to be taken to avoid surface degradation 22 . Chemically grown silver nanowires have been successfully coupled with visible quantum emitters 4,23,24 .…”
mentioning
confidence: 99%
“…This drastically restricts the choice of emitters available for quantum plasmonic experiments [16][17][18] . In contrast to gold, silver leads to reduced losses in the visible spectral range [19][20][21] although care has to be taken to avoid surface degradation 22 . Chemically grown silver nanowires have been successfully coupled with visible quantum emitters 4,23,24 .…”
mentioning
confidence: 99%
“…When a Ag NW network is directly exposed to ambient conditions, atmospheric sulfur such as hydrogen sulfide (H2S) or carbonyl sulfide (OCS) can easily react with the intrinsic defect structure of the Ag NW pentagon, which leads to a significant increase in electrical resistance. [32][33][34][35][36] This is one of the most important issues with Ag NW networks for practical applications. We also track the When a Ag NW network is directly exposed to ambient conditions, atmospheric sulfur such as hydrogen sulfide (H 2 S) or carbonyl sulfide (OCS) can easily react with the intrinsic defect structure of the Ag NW pentagon, which leads to a significant increase in electrical resistance.…”
Section: Resultsmentioning
confidence: 99%
“…It turns out that the presence of water in air is of prime importance. Several other papers also reported that both sulfidation and oxidation require humidity to take place [38][39][40][41].…”
Section: Evolution Of the Ag 0 Particles In Airmentioning
confidence: 96%